Maternal Diabetes Modulates Renal Morphogenesis in Offspring - Stella Tran; Yun-Wen Chen; Isabelle Chénier; John S.D. Chan; Susan E. Quaggin; Marie-JoseCombining Acute Accente HeCombining Acute Accentbert; Julie R. Ingelfinger; Shaoling Zhang (2008)
Maternal diabetes leads to an adverse in utero environment, but whether maternal diabetes impairs nephrogenesis is unknown. Diabetes was induced with streptozotocin in pregnant Hoxb7-green fluorescence protein mice at embryonic day 13, and the offspring were examined at several time points after birth. Compared with offspring of nondiabetic controls, offspring of diabetic mice had lower body weight, body size, kidney weight, and nephron number. The observed renal dysmorphogenesis may be the result of increased apoptosis, because immunohistochemical analysis revealed significantly more apoptotic podocytes as well as increased active caspase-3 immunostaining in the renal tubules compared with control mice. Regarding potential mediators of these differences, offspring of diabetic mice had increased expression of intrarenal angiotensinogen and renin mRNA, upregulation of NF-kappaB isoforms p50 and p65, and activation of the NF-kappaB pathway. In conclusion, maternal diabetes impairs nephrogenesis, possibly via enhanced intrarenal activation of the renin-angiotensin system and NF-kappaB signaling.